Análisis energético de un sistema de generación híbrida - eólico pila de combustible por electrolizador de mediana producción para la empresa RS ROTH S.A. Sector Calderón, provincia de Pichincha, durante el período 2014-2015. Propuesta de factibilidad económica y técnica del sistema para la reducción del consumo de la red eléctrica. - Gallardo Cárdenas, Félix Fabián (2016)
The present investigation approaches subjects as energetic efficiency inside industrial environments, besides of the efficient implementation on big announcement places like the represented by RS Roth S.A., Calderón sector, Pichincha providence, during 2014 – 2015 trough the study of a complex hybrid electric supplying system with participation of wind power uptake, electrolyzing processes and fuel cells. The main object of this study is with a previous theoretical investigation, along with a methodological specific frame for recollection and analysis of wind power and fuel cell energetic transformation data, to provide a proposal specific frame to achieve the RS Roth S.A. goals, mainly about the electricity consumption reduction through the self-provisioning, based directly to a reduction of direct financial resources, as well as the investigative immersion inside production fields with participation of electrolysers and fuel cells. Initially, there was made a bibliographic request of wind power uptake information, electrolyzing for hydrogen production, as well as their storage into pressurized deposits for usage in energy production by the fuel cell. Later, there was selected the technology that provides the more benefits inside the hybrid energetic structure. This technology at the end is subjected to feasibility analysis to present into economical aspects, the utility of the hybrid electric supplying system inside the factory, with items of production, energetic efficiency and return of the investment, as well as the environmental affection.